Interprofessional Differences in Multidimensional Self-Efficacy Associated With Professional Performance in Nephrology During Case-Based Learning - Chia-Ter Chao; Mei-Yi Wu; Kuan-Yu Hung; Mai-Szu Wu; Jyh-Chong Liang (Kidney International Reports)
Introduction: Postgraduate medical education assumes rising importance in the rapidly advancing field of medicine. Case-based learning (CBL), a learner-centered pedagogy employing clinical cases to improve decision-making, is widely embraced in postgraduate medical education, including nephrology. Studies suggest that learning self-efficacy (SE) was closely associated with learning motivation and academic performance; however, very few studies examined this association in postgraduate nephrology education. None evaluated whether there were interprofessional differences concerning such association. Methods: In 2022, we prospectively enrolled physicians and nurses participating in chronic kidney disease (CKD) care from institutions around Taiwan. They completed the Professional Medical Learning Self-efficacy (PMLS) questionnaire after attending >1 CBL session involving CKD care. We undertook confirmatory factor analysis (CFA), followed by structural equation modeling (SEM) to evaluate associations between 5 dimensions of learning SE (conceptual understanding [CU], higher-order cognitive skills [HC], practical work [PW], everyday application [EA], and medical science communication [MSC]) and their professional SE in nephrology according to participants' medical professions. Results: A total of 513 healthcare providers were surveyed. The convergent and construct validity of our questionnaire were satisfied after analyses. We found that better perceived professional performance in the form of higher professional SE in nephrology was significantly associated with all 5 dimensions of learning SE among physicians and nurses. Only CU and PW were significantly associated with physicians' professional performance; whereas among nurses, only HC and MSC were significantly associated. Conclusion: We showed that learning SE was an important determinant of nephrology professional performance. Different medical professions posed influences on major SE dimensions.